The Strong Positive Correlation between Factor VII Clotting Activity Using Bovine Thromboplastin and the Activated Factor VII Level - Kario, Kazuomi; Matsuo, Takefumi; Asada, Reiko; Sakata, Toshiyuki; Kato, Hisao; Miyata, Toshiyuk (Thrombosis and Haemostasis, 1995)
We compared factor VII clotting activity (FVIIc) assays using different thromboplastins to determine which is the most sensitive for activated FVII (FVIIa) or for FVII antigen (FVIIag). FVIIc levels were measured using thromboplastins derived from bovine brain (FVIIc Bov), human placenta (FVIIc Hum), and rabbit brain (FVIIc Rab). FVIIa levels were measured by fluorogenic assays using human soluble tissue factor (rsTF) or bovine rsTF. We also measured FVII activity by an amidolytic assay (FVIIc:am Hum) using human thromboplastin and a chromogenic substrate for thrombin. FVIIag levels were determined by ELISA. In the FVIIa assay, the reaction time obtained from using bovine rsTF was shorter than that with human rsTF, suggesting that the interaction of plasma FVIIa with bovine rsTF was stronger than with human rsTF. The plasma FVIIa levels measured using human rsTF and bovine rsTF were almost the same (r=0.947, p<0.0001). Among the three FVIIc assays, FVIIc Bov had the strongest positive correlation with the plasma FVIIa level (r=0.886, p<0.000l), but had no correlation with FVIIag. An increase of 1 ng/ml in the plasma FVIIa level yielded a 27.9% increase of FVIIc Bov. Plasma FVIIc Hum and FVIIc:am Hum showed moderate correlations with both FVIIa (r=0.520, p<0.02 and r=0.569, p<0.01, respectively) and FVIIag (r=0.438, p<0.05 and r=0.468, p<0.05, respectively). FVIIc Rab had the lowest correlation with FVIIa (r=0.367, p<0.1), but had a moderate correlation with FVIIag (r=0.436, p<0.05). After in vitro cold activation, FVIIc Bov levels increased the most and FVIIc:am levels showed the least change. These findings indicate that consideration of the thromboplastin used for assay is necessary when assessing the clinical significance of FVII activity as a cardiovascular risk factor.